Orgies of Feeling : Melodrama and the Politics of Freedom - Anker, Elisabeth R. (Book collections on Project MUSE., 2014)
Analyzing the work of melodrama and affect in contemporary politics, Elisabeth R. Anker boldly reframes political theories of sovereignty, freedom, and power. Through readings of melodramatic discourses in the War on Terror, neoliberal politics, anticommunist rhetoric, Hollywood film, and post-Marxist critical theory, she argues that melodrama animates desires for unconstrained power.